2021
DOI: 10.1021/acsomega.0c04250
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the CO2 Huff and Puff Effect in Low-Permeability Sandstones with NMR

Abstract: For low-permeability sandstone reservoirs, CO 2 huff and puff is an effective method for increasing oil recovery. Commonly, sandstone formations with low permeability have diverse pore and throat sizes and a complex pore-throat structure, which essentially affects the flow characteristics of CO 2 and oil in the formation and further the CO 2 huff and puff performance. It is necessary to understand the recovery degree of various microscale pore sizes under different operational parameters during CO 2 huff and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…54 When considering a fixed overall operating duration for recovery, however, shorter soak times and shorter puff times can result in better oil recovery, because more cycles can be done. In 2021, Zhao et al 279 discovered that, as the cycle number increases, the cyclic oil recovery diminishes, with the first cycle producing the majority of the oil. They indicated that the cycle number of CO 2 H-n-P should not exceed 3 under the experimental conditions of that kind of study.…”
Section: Gas-eor Experimental Studiesmentioning
confidence: 99%
“…54 When considering a fixed overall operating duration for recovery, however, shorter soak times and shorter puff times can result in better oil recovery, because more cycles can be done. In 2021, Zhao et al 279 discovered that, as the cycle number increases, the cyclic oil recovery diminishes, with the first cycle producing the majority of the oil. They indicated that the cycle number of CO 2 H-n-P should not exceed 3 under the experimental conditions of that kind of study.…”
Section: Gas-eor Experimental Studiesmentioning
confidence: 99%
“…The distribution of the T 2 spectrum corresponds well with the pore distribution determined by the mercury intrusion experiment, and both show two wave peaks. In general, the pores can be classified into three categories based on the transverse relaxation time T 2 : , micropores, T 2 < 10 ms, corresponding to a pore radius r < 0.332 μm; mesopores, 10 ms < T 2 < 100 ms, corresponding to a pore radius of 0.332 μm < r < 3.320 μm; macropores, T 2 > 100 ms, corresponding to a pore radius r > 3.320 μm.…”
Section: Methodsmentioning
confidence: 99%
“…As a general rule, micropores have a relaxation time between 0 and 1 ms. Small pores, medium pores, and macropores are defined as those with relaxation times of 1–10 ms, 10–100 ms, and greater than 100 ms, respectively. The true pore classification method was used and is based on the pore classification types identified in earlier studies in shale reservoirs. In compliance with NMR test and the current pore classification standard, the pores of experimental cores are divided into four categories: micropores (>0–007 μm), small pores (0.007–0.07 μm), medium pores (0.07–0.7 μm), and macropores (≫0.7 μm) on the scale of T 2 , as shown in Table . The remaining residual oil distribution during CO 2 HnP cycles can be studied using NMR spectroscopy to see how varying pore sizes affect enhanced oil recovery and the recovery factor in each pore size when different cycle numbers are used.…”
Section: Methodsmentioning
confidence: 99%
“…50−52 In compliance with NMR test and the current pore classification standard, the pores of experimental cores are divided into four categories: micropores (>0−007 μm), small pores (0.007−0.07 μm), medium pores (0.07−0.7 μm), and macropores (≫0.7 μm) on the scale of T 2 , as shown in Table 4. 52 The remaining residual oil distribution during CO 2 HnP cycles can be studied using NMR spectroscopy to see how varying pore sizes affect enhanced oil recovery and the recovery factor in each pore size when different cycle numbers are used.…”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%